Development of a Minangkabau Culture-based e-LKPD to Enhance Cultural and Civic Literacy: An ADDIE Approach in Social Science Study at Elementary School - Rendy Nugraha Frasandy; Mesi Julina Putri; Nyangfah Nisa Septiana; Exsaris Januar; Rovika Meisya (JIP Jurnal Ilmiah PGMI, 2025)
The purpose of this study was to develop teaching materials in the form of e-LKPD for Natural and Social Science (IPAS) subjects  containing Minangkabau culture through project–based learning for cultural and citizenship literacy that is valid, practical and effective. The research was conducted at Khaira Ummah Islamic Elementary School, Padang. The subjects in this study were 3 validators, one teacher and 28 fourth–grade students. This study applied research and development with an ADDIE model. The instruments used were validity and practicality questionnaires and effectiveness test questions. The results of the study showed that the validity was very high with a score of 92%, with a material feasibility percentage of 93%, language feasibility of 91% and media feasibility of 92%. The product practicality test was 84% in the very practical category. Meanwhile, the effectiveness test was in the effective state with an average score of 70.17%  medium category. In educational practice, the developed e-LKPD can serve as a model for integrating local culture into learning materials to support the achievement of SDG 4 (Quality Education) and to promote character education based on cultural values. Teachers can utilize the e-LKPD as a learning innovation that bridges local cultural wisdom with modern learning approaches, particularly project-based learning.